Nonlinear dynamic analysis of wind pressure variability on standard tall building - He, YH; Shu, ZR; Chen, FB; Liu, HM (Advances in structural engineering, 2023)
Understanding the variability of wind pressure on tall building surfaces is of essential importance regarding the control of wind-induced response. In this study, advanced time series analysis techniques, e.g., phase space reconstruction and recurrence analysis, were applied to diagnose the wind pressure variability from a nonlinear dynamic perspective. It is shown that, the wind pressure acting on tall building surfaces exhibit distinct chaotic nature. Due to the complex flow patterns around the building, the underlying dynamics of wind pressure is subject to pronounced region-to-region variability. For windward surface, the wind pressure dynamics at the stagnation region is more deterministic than those of downstream. For the side surfaces, the distribution of recurrence quantification analysis (RQA) indicators follows a clear pattern, where the values are larger at the near-front edge, and decreases towards the rear. The distribution of RQA indicators on the leeward surface is opposite to that of windward surface, in which larger values occur more often at near-ground level. Further upstream, the values are found to decrease. The outcomes provide valuable insights to the wind-structural interaction, thus could help wind-resistant design.